Military Policy of the Republic of Moldova 1991-2011 years - Bogdan Levyk (Cхід, 2013)
Military and historical analysis behind the background of creating the armed forces of Moldova, its defence policy in the region and international stage has been carried out, as well as examination of the groundlaying legislative acts guaranteeing the security sphere. Military potential of Moldavian armed forces has been evaluated, while bilateral Ukrainian-Moldavian relations have been summarized.